Rhetoric, Reality and Racism: The Governance of Aboriginal and Torres Strait Islander Health Workers in a State Government Health Service in Australia - Stephanie Topp; Josslyn Tully; Rachel Cummins; Veronica Graham; Aryati Yashadhana; Lana Elliott; Sean Taylor (International Journal of Health Policy and Management, 2022)
Background  In northern Australia, Aboriginal and Torres Strait Islander Health Workers (A&TSIHWs) are unique members of nominally integrated teams of primary care professionals. Spurred by research documenting ongoing structural violence experienced by Indigenous health providers and more recent challenges to recruitment and retention of A&TSIHWs, this study aimed to explore whether the governance of the A&TSIHW role supports full and meaningful participation.Methods  The qualitative study was co-designed by a team of Aboriginal, Torres Strait Islander and non-Indigenous collaborators. Data collection comprised document review and interviews with A&TSIHWs (n = 51), clinicians (n = 19) community members (n = 8) and administrators (n = 5) in a north Queensland health district. We analysed governance at multiple levels (regulatory, organisational, and socio-cultural) and used critical race theory to deepen exploration of the role of race and racism in shaping it.Results  Governance of the A&TSIHW role occurs within a health system where racism is built into, and amplified by, formal and informal rules at all levels. Racially discriminatory structures such as the previous but long-standing relegation of A&TSIHW into the same career stream as cleaners were mirrored in discriminatory rules and managerial practices such as an absence of career-specific corporate support and limited opportunities to participate in, or represent to, key leadership groups. These interacted with and helped perpetuate workplace norms permissive of disrespect and abuse by non-Indigenous professionals. Ongoing resistance to the structural violence required of, and demonstrated by A&TSIHWs speaks to the gap between rhetoric and reality of governance for A&TSIHWs.Conclusion  Strengthening governance to support A&TSIHWs requires critical attention be given to the role of race and racism in regulatory structures, organisational practice, and inter-professional relationships. Addressing all domains will be essential to achieve systemic change that recognises, supports and embeds the unique knowledge, skills and functions of the A&TSIHW role.